1937
DOI: 10.1098/rspa.1937.0032
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of trebly-ionized lead, Pb IV

Abstract: Carroll, Smith, Rao and Narayan and Schoepfle have established terms of the one-electron configurations of Pb IV. Schoepfle, whose analysis is the most complete, has identified the 6 s , 7 s , 8 s , 6 p 7 p , 6 d , 7 d , 5 f doublets, and in addition assigned a number of terms to the many-electron configurations that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

1955
1955
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
4
15
0
1
Order By: Relevance
“…Обширные данные по изотопическому смещению в линиях и термах свинца собраны для РЬI и РЬ Ц180-Ю4, р Ь щаяв и РЬIV 186 , которые в обобщённом виде даны в таблицах Брикса и Копфермана 12 . В термах свинца проявляются те же закономер- Большое внимание за последние годы было уделено исследо-ванию изотопического смещения в спектрах элементов редкозе-мельного ряда.…”
Section: а р стриганов и ю п донцовunclassified
“…Обширные данные по изотопическому смещению в линиях и термах свинца собраны для РЬI и РЬ Ц180-Ю4, р Ь щаяв и РЬIV 186 , которые в обобщённом виде даны в таблицах Брикса и Копфермана 12 . В термах свинца проявляются те же закономер- Большое внимание за последние годы было уделено исследо-ванию изотопического смещения в спектрах элементов редкозе-мельного ряда.…”
Section: а р стриганов и ю п донцовunclassified
“…In this previous work we used relativistic Hartree-Fock (HFR) calculations to obtain the oscillator strengths, but no core-polarization effects were included in these calculations. The Pb IV spectrum was studied earlier in the range from 200 to 9000 Á by Schoepfle [5] and Crawford et al [6]. Analyses of transitions from the autoionizing states 5d 9 6s nf (n = 5,6,7) to the 5d 10 6s 2 S 1/2 in Pb IV have also been reported [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the Table 2). Transitions are taken from Crawford et al (1937) and Gutmann (1969). intensity ratios of the Pb IV spectral lines are constant (within 14%) during the plasma decay.…”
Section: Methodsmentioning
confidence: 99%
“…A pulsed discharge was created in a glass discharge tube of 5 mm inner diameter with a plasma length of 14 cm (see Fig. 1 Zaidelj et al (1977) not classified by ionization stages, while (Craw) is the abbreviation for Crawford et al (1937) and (Smith) for Smith (1930). of the plates provides uniform distribution of the sputtered Pb atoms along the optical axis of the homogeneous part of the discharge. The length of the cylindrical plates is 20 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation